The Potency of Organic Fertilizer in Reducing Leaf Curl Disease on Chili (Capsicum annuum L.): Potensi Pupuk Organik Dalam Mengurangi Penyakit Keriting Daun Pada Cabai (Capsicum annuum L.) - Subiastuti, Aprilia Sufi; Windianingsih, Diah Fitri; Noviyani, Pipit; Kusnanda, Prima Sekti (Department of Biology Faculty of Mathematics and Natural Sciences Universitas Lampung in collaboration with The Indonesian Association of Biology (PBI) Lampung Branch., 2025)
Chili is an essential commodity in Indonesia, with demand continuing to rise; however, its production is often disrupted by leaf curl disease caused by viruses. One potential solution is using organic fertilizer enriched with beneficial microbes such as Plant Growth-Promoting Microorganisms (PGPM). Despite its potential, the role of PGPM in controlling viral diseases in chili plants has been rarely studied. This study aims to explore the effectiveness of organic fertilizer in reducing leaf curl infections by improving plant health. Two chili cultivars were used: 'Gama LBF' (a breeding product of PIAT UGM) and 'Ponirun' (a commercial variety known for its disease resistance). The chili plants were treated with various concentrations of organic fertilizer, and their effectiveness was evaluated based on disease incidence (the number of symptomatic plants) and disease severity (the level of visual symptoms), which were then converted into an index. Results showed that the 75% concentration yielded the lowest disease incidence in both cultivars—26.5% for 'Ponirun' and 42.85% for 'Gama LBF'. The lowest disease severity was also observed at the 75% concentration for 'Ponirun' and 50% for 'Gama LBF'. These findings highlight the importance of selecting the appropriate organic fertilizer concentration to suppress leaf curl disease in chili effectively.